Large scale direct galaxy collision simulations with central supermassive binary black holes. Issue Volume 10:Issue S312(2014) (7th March 2016) - Sobolenko, Margaryta; Berczik, Peter; Spurzem, Rainer
Abstract: We present a set of, large scale direct N -body simulations of the galaxy collision with the central Supermassive Black Hole Binary (SMBHB) system. Based on our simulations which include the accurate Post Newtonian (PN) relativistic dynamical corrections we can estimated the merging time for the real astrophysical object. Each galaxy initially was represented as a set of particles (up to N=500k) with Plummer distribution. The SMBHBs system is described using the two special high mass, i.e. "relativistic", particles. The interaction between these two particles have an extra PN correction terms (up to 3.5PN). Merging time upper limit was obtained for the closely interacting galaxy system NGC 6240.